Links between Folkcommunication and Functionalism - Parente Aragão, Iury (2016)
This article focuses on the initial ideas of Luiz Beltrão about folkcommunication (1967) and discusses the interpretation about the theoretical basis of this field is the functionalism. For this research was chosen a literature review and the reading of works sources (in the sense suggested by Ruiz, 2002), to verify the bonds between folkcommunication and functionalism (or if they even exist). After the examination of the thesis that led to folkcommunication and of the characteristics in the paper works of the main functionalist authors mentioned in the Beltrão’s thesis, the results point that the hypothesis that the folkcommunication is related to functionalism does not hold.